1987
DOI: 10.1111/j.1151-2916.1987.tb04949.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformations in the Decomposition of Mg(OH)2 and MgCO3

Abstract: A transmission electron microscopy study has been carried out to understand the structural transformation mechanisms of decomposition of Mg(OH)2 and MgC03 under vacuum. Both Mg(OH)2 and MgC03 decompose topotactically to yield porous pseudomorphic MgO of normal structure with definite orientation relationships. The decomposition of Mg(OH)2 yields MgO with a single orientation relationship, but that of MgC03 leads to one major and two minor orientation relationships with two, six, and three variants, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0
5

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 14 publications
11
67
0
5
Order By: Relevance
“…Even then, some MgO nanocrystals were observed in the reaction layer due to MgCO 3 decomposition to MgO + CO 2 (g) during sample thinning and/or electron-beam observation. This follows from the high sensitivity of MgCO 3 to decomposition via electron and ion beam exposure, 9 as demonstrated for single crystal MgCO 3 reference materials herein, especially when the carbonate is in nanocrystalline form. These studies indicate the silica-rich passivating layers that form during carbonation can effectively trap magnesite nuclei that form during carbonation.…”
Section: Resultsmentioning
confidence: 99%
“…Even then, some MgO nanocrystals were observed in the reaction layer due to MgCO 3 decomposition to MgO + CO 2 (g) during sample thinning and/or electron-beam observation. This follows from the high sensitivity of MgCO 3 to decomposition via electron and ion beam exposure, 9 as demonstrated for single crystal MgCO 3 reference materials herein, especially when the carbonate is in nanocrystalline form. These studies indicate the silica-rich passivating layers that form during carbonation can effectively trap magnesite nuclei that form during carbonation.…”
Section: Resultsmentioning
confidence: 99%
“…Layer permeability is critical for PL formation via incongruent dissolution, as it facilitates both the transport of Mg ions through the layer and the formation of water and its expulsion from the layer. Close examination of the simulated PL structure suggests that even without allowing for the structural disruption associated with >Si-OH formation, it may be permeable to key species 34 associated with mineral carbonation (e.g., Mg 2+ , H + , and H 2 O), consistent with incongruent dissolution. Such permeability does not exist in our quenched thermal SiO 2 glass model, but is found for the simulated PL structures.…”
Section: Simulation Of Passivating Layer Formationmentioning
confidence: 99%
“…Both processes readily cause decomposition to MgO, consistent with earlier electron irradiation observations made on bulk MgCO 3 . 34 Thus, the nanoparticles that formed during carbonation were MgCO 3 . The MgO particles observed are artifacts formed by MgCO 3 decomposition during specimen preparation or electron beam observation.…”
Section: Controlled Particle Abrasion: Enhancing Passivating Layer Exmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains that why the observed decomposition produces (MgO) of magnesite are cube nano-particles. Kim et al [26] observed the structures of larger MgO clusters by using transmission electron microscopy and found that the cube-like nanoparticles with the edge length 2-3 nm.…”
Section: Growth Strategies Of (Mgo) N Clustersmentioning
confidence: 99%